Synthesis, characterization and biological studies of some piperazines and their metal complexes / Muhammad Saleh Salga - Salga, Muhammad Saleh (2012)
Piperazine derived Schiff bases were synthesized by an ethanolic condensation of 2- (piperazin-1-yl)ethanamine with either salicylaldehyde (LSP), 5-chlorosalicylaldehyde (LCS), 5-bromosalicylaldehyde (LBS), 5-nitrosalicylaldehyde (LNS), 5-hydroxy salicylaldehyde (LDH), 4-hydroxysalicylaldehyde (DHS), 5-methoxysalicylaldehyde (LHM) or 4-methoxysalicylaldehyde (HMS). Other Schiff bases were obtained from 1-(2- hydroxyphenyl)ethanone (2HP) and 1-(2,4-dihydroxyphenyl)ethanone (DHP). Schiff basemetal complexes of Cu(II), Zn(II) and Cd(II) were prepared by direct synthesis which yielded 1:1 metal-ligand ratio. The solid product formed was collected, washed with ethanol, recrystallized from suitable solvent and dried in a vacuum desiccator. The Schiff bases and their metal complexes were fully characterized by spectroscopic methods such as IR, 1H NMR, 13C NMR and UV-visible. Thermal studies (TGA) on the complexes were carried out and structural studies on suitable single crystals were performed using x-ray crystallography technique. Other purification determination techniques employed involved elemental analysis, mass spectroscopy and melting point determination. The X-ray diffraction analyses were conducted on CdLS, CdLHM, ZnHMS, ZnLDH and ZnLNS. The analytical data demonstrated the flexidentate behavior of the Schiff bases upon complexation, forming chair conformations with highly distorted square pyramidal geometries in most of the compounds. The synthesized Schiff bases and their complexes were screened in-vivo (acute toxicity and gastro-protective activity) and in-vitro (antioxidant, anti-cancer acetylcholinesterase inhibition and molecular modeling activities). The compounds exhibited good biological activities in most of the studies.